2000
DOI: 10.1111/j.8755-8920.2000.440608.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Functional Chemokine Receptors of Human Placental Cells

Abstract: Our results suggest possible roles of chemokines/chemokine receptors on placental physiology and their involvement in HIV transmission as alternative receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…28 CCR6 is essential for the migration of Th17 cells. 29,30 Human placental cells express a series of functional chemokines, 31 and we speculate that placental cells may attract peripheral Th17 cells into decidua. It has been demonstrated that DSCs other than trophoblasts recruit peripheral Th17 cell into decidua.…”
Section: Discussionmentioning
confidence: 88%
“…28 CCR6 is essential for the migration of Th17 cells. 29,30 Human placental cells express a series of functional chemokines, 31 and we speculate that placental cells may attract peripheral Th17 cells into decidua. It has been demonstrated that DSCs other than trophoblasts recruit peripheral Th17 cell into decidua.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, mRNA for these chemokines was expressed predominantly in the decidual samples and almost undetectable in their chorionic counterparts. Using RT-PCR, Ishii et al demonstrated mRNAs for RANTES, MIP-1α and MCP-3 in chorionic samples from the first trimester (Ishii et al, 2000). This apparent discrepancy might be due to differences in PCR conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Placental tissues (6-9 weeks of gestation, n=15) CCR1 595 CTCTTCCTGTTCACGCTTCC CCAAATGTCTGCTCTGCTCA NM_001295 CCR2 600 AACTCCTGCCTCCGCTCTAC TCACTGCCCTATGCCTCTTC XM_002924 CCR3 588 TCTTCCTCGTCACCCTTCCA GCTTCGTCCGCTCACAGTCA AB023887 CCR4 608 CTTCCTGCCCCCACTGTATT TCTTCACCGCCTTGTTCTTC NM_005508 CCR5 818 TCCTGCCTCCGCTCTACT GAACTTCTCCCCGACAAA XM_002925 CCR6 609 AATCATCTGCCTTGTTGTGT TTGTCGTTATCTGCGGTCTC NM_004367 CCR7 581 TGGCTCTCCTTGTCATTTTC TTGCTCACTGCTGCTCCTCT NM_001838 CCR8* 286 AGTATGCACATCTTGGATGG TGTAGTCTACGCTGGAGGAA U45983 CCR9 580 CCAAGCACAAAGCCCTAAAA CAGTCAAGAGCCAATCAACA AF145440 CCR10* 493 GGGTTTCTCCTTCCACTCCT TATTCCCCACATCCTCCTTG U94888 CCR11 450 *Primer pairs were taken from published articles (Kojima et al, 1994;Jordan et al, 1999;Ishii et al, 2000;Middel et al, 2001;Huber et al, 2002;Kawaguchi et al, 2002). were washed with sterile RPMI and dissected aseptically to remove decidual tissues and fetal membrane. Small fragments of chorionic villi (∼2 mm in diameter) were teased apart and soaked in culture medium [RPMI containing 10% FCS (Gibco), 100 U ml −1 penicillin and 100 µg ml −1 streptomycin (Gibco)].…”
Section: Human Chorionic Villous Explant Culture and Isolation Of Evtsmentioning
confidence: 99%
See 2 more Smart Citations